Place of Serology in the Diagnosis of Zoonotic Leishmaniases With a Focus on Visceral Leishmaniasis Due to Leishmania infantum - Maude F. Lévêque; Laurence Lachaud; Loïc Simon; Emilie Battery; Pierre Marty; Christelle Pomares (Frontiers in Cellular and Infection Microbiology, 2020)
Leishmaniases are a group of parasitic diseases transmitted through the bite of female phlebotomine sandflies. Depending on the Leishmania species, the reservoirs can be humans (anthroponosis) or different animals (zoonosis). Zoonotic leishmaniasis present several clinical forms in function of the species involved: visceral leishmaniasis (VL), cutaneous leishmaniasis (CL), and muco-cutaneous leishmaniasis (MCL). The biological diagnosis is of utmost importance because the clinical features are not specific. In addition to parasitological and molecular biology (polymerase chain reaction, PCR) assays, serology is routinely used for the diagnosis of leishmaniasis. Indeed, although PCR is more sensitive than serological assays, its implementation is limited to referral laboratories and research centers. Therefore, serology is still a key element for their diagnosis. Here, we discuss the different serological assays available for the diagnosis of zoonotic leishmaniasis. We will review the enzyme-linked immunosorbent assay, immunofluorescence antibody test, immunochromatography test (ICT), direct agglutination test, and western blot as well as the different diagnostic strategies in function of the clinical form (VL, CL, and MCL). We will also discuss the place of serology for detecting asymptomatic carriers and for the follow-up of VL. Depending on the laboratory, different assays can be used, from ICT, which is appropriate for field testing, to a combination of serological tests to improve the sensitivity.